Garcinia latissima Miq. Leaves and Some of Its Activities - Ambarwati, Neneng Siti Silfi; Triyani, Yulia (Pharmaceutical Science: New Insights and Developments Vol. 1, 2024)
Background: Plants are known to contain bioactive compounds that offer a range of health benefits. The Garcinia species, particularly, are recognized for their diverse biological activities, such as antioxidant, anti-elastase, anti-tyrosinase, and antibacterial properties. These activities are crucial for maintaining overall health, protecting against oxidative stress, preventing skin aging, and combating infections. While numerous studies have explored various Garcinia species, Garcinia latissima Miq. has yet to be investigated. This study aims to explore the antioxidant, anti-elastase, anti-tyrosinase, and antibacterial activities of Garcinia latissima Miq. leaves, as well as identify active isolates from the leaves, which could contribute to developing therapeutic agents for managing oxidative damage, skin conditions, and bacterial infections. Aims: This study explores the antioxidant, anti-elastase, anti-tyrosinase, and antibacterial activities of Garcinia latissima Miq. leaves and isolates the compounds responsible for these effects. Methodology: Extraction was performed using stepwise maceration with methanol, n-hexane, and ethyl acetate, followed by fractionation through column chromatography. Antioxidant activity was evaluated using DPPH and FRAP assays, anti-elastase activity through spectrophotometry with PPE and SANA, and antibacterial activity via microdilution. The anti-tyrosinase activity was quantified spectrophotometrically using L-DOPA. Active fractions were isolated and identified by NMR analysis. Results: The ethyl acetate extract showed the highest DPPH inhibition (IC50 = 86.91 \(μ\)g/mL). In antibacterial tests, the methanol extract exhibited a significantly larger inhibition zone against Bacillus subtilis (9.9 ± 0.786 mm) compared to the ethyl acetate extract (7.68 ± 0.076 mm). NMR analysis identified friedelin as the active compound in the ethyl acetate fraction and amentoflavone in the methanol extract fraction. Conclusion: Garcinia latissima Miq. leaves demonstrated significant antioxidant activity in both the extract and its fractions. NMR analysis identified friedelin as the active compound in the ethyl acetate extract fraction, while amentoflavone was isolated from the methanol extract fraction. These findings highlight the potential of G. latissima leaves as a source of bioactive compounds with therapeutic applications.